Gender leadership and excellence: The case of higher education in Lebanon - Noha Hamie Haidar (Administrative Sciences, 2018)
This study aimed to explore the employment status of women in the higher educational sector and to uphold women's productivity and commitment in executive positions of responsibility. Management tended to show preferential treatment for men in top management positions; hence, women were less engaged in the decision-making process. Women possess the potential to be transformative leaders in higher education institutions (HEI). The research purpose of this study was to speculate that some Lebanese educational institutions still practice discrimination and prefer men over women in executive positions, as well as to show that excellence in educational institutions is linked to women being in these executive positions. Currently, the higher education sector in Lebanon is under development as numerous educational developments are being implemented. The problem is that a peculiar attitude toward women in the HEI sector and specifically in top management positions still exists. In this study, the author explored women's engagement at the top levels of higher education management and found that only 15 out of 65 Dean's positions were filled by women and aimed to discover the factors behind the misrepresentation of women within the higher education system in Lebanon. In addition, the study found a positive relationship between the presence of women and the performance of HEIs. In this study, I aimed to focus on women's engagement at the top management level and to emphasize the advantages of their skills and expertise, as well as to enhance the presence of women. The findings were significant and clear: There was misrepresentation, bias and stereotyping in HEIs. A clear strategic plan is needed to engage women in the decision-making process along with a well-designed incentive plan to achieve the required purpose. The aim of this study was to highlight this matter and to accentuate the benefit of women's leadership roles in higher education in Lebanon. A qualitative strategy was used: Primary information was obtained from interviews with 12 chairpersons at six different schools. Data were gathered and analyzed to provide insightful results and recommendations.
Keywords: 350; gender leadership; higher education; women leadership